2022
DOI: 10.1186/s13643-022-02061-9
|View full text |Cite
|
Sign up to set email alerts
|

A realist review protocol on communications for community engagement in maternal and newborn health programmes in low- and middle-income countries

Abstract: Background Community engagement (CE) has been increasingly implemented across health interventions, including for maternal and newborn health (MNH). This may take various forms, from participatory women’s groups and community health committees to public advocacy days. While research suggests a positive influence of CE on MNH outcomes, such as mortality or care-seeking behaviour, there is a need for further evidence on the processes of CE in different settings in order to inform the future devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Despite the agreement on the positive implications of CE, the literature relating to which CE approaches are most effective and how to incorporate them across settings is limited ( O’Mara-Eves et al , 2013 ; Dada et al , 2021b ; 2022 ). Proposed frameworks and principles of CE suggest the importance of characteristics such as adaptability, reciprocity, relatability, relationships, respect, trust and transparency ( Noorani and Gubb, 2007 ; Geissler et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the agreement on the positive implications of CE, the literature relating to which CE approaches are most effective and how to incorporate them across settings is limited ( O’Mara-Eves et al , 2013 ; Dada et al , 2021b ; 2022 ). Proposed frameworks and principles of CE suggest the importance of characteristics such as adaptability, reciprocity, relatability, relationships, respect, trust and transparency ( Noorani and Gubb, 2007 ; Geissler et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2016 ). Despite the availability of these frameworks for effective communication and the understanding that it is important in health interventions, there is little specific discussion on how communication is used, designed and implemented within CE strategies ( Dada et al , 2021b ; 2022 ; 2023a ). CE and its communications aspects are complex, involving multiple interacting components and spanning a range of levels of involvement ( Gilmore et al , 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The realist review is iterative, making it less linear or rigid than a traditional systematic review. 10,11 The steps of a realist review, demonstrated in Figure 1, are guided by the four approaches to inference-making in realistinformed inquiries: induction, abduction, deduction and retroduction. 12 Inductive thinking involves projecting from what we know to what we do not know and is also applied to identify patterns in the evidence to draw conclusions.…”
Section: The Realist Reviewmentioning
confidence: 99%
“…• Author A: The challenge of determining approaches to richness and rigour (11) When determining the criteria for selecting sources to be included in my realist review and assessing them, I struggled to find detailed examples in the literature of how to go about this. I developed relevance criteria as I would for a traditional systematic review, and built off of this for 'richness' criteria by asking more specific questions about the level of depth or detail the source provided for each of the topic areas of my inclusion criteria.…”
Section: Assessing Rigourmentioning
confidence: 99%
See 1 more Smart Citation